Prediction model of low cycle fatigue life of 304 stainless steel based on genetic algorithm optimized BP neural network - Mengjie Cao; Hongyan Duan; Hong He; Yang Liu; Shunqiang Yue; Zengwang Zhang; Yingjian Zhao (Materials Research Express, 2022)
The low cycle fatigue life of 304 stainless steel is an essential basis for safety assessment. Usually, there is a complex nonlinear relationship between fatigue life and influencing factors, which is difficult to be predicted by traditional fatigue life models. Based on this, the BP algorithm and genetic optimization algorithm (GA) for the fatigue life prediction problem of 304 stainless steel is proposed. Based on the existing large amount of test data, the fatigue life of 304 stainless steel material is predicted by using BP and GA-BP learning models. The results show that the GA-BP prediction model is more flexible, the correlation coefficient R reaches 0.98158, the prediction data are within the 2 times error limit and closer to the ideal line, and the model prediction is better.